Shoulder and elbow surgery - Lee, Donald H; Neviaser, Robert J (Elsevier, 2019)
This fully revised title brings you up to speed with must-know surgical techniques in today ́s technically demanding shoulder and elbow surgery. Nakladatelská anotace. Kráceno
Operative techniques
Keywords: ortopedie; chirurgie; Shoulder; Elbow; loket; rameno